A LIVING TEMPLE - (PHAD PAINTING IN RAJASTHAN) - Mahawar, Krishna (International Journal of Research -GRANTHAALAYAH, 2018)
I consider Phad Painting as a valuable pilgrimage of Rajasthan. Phad painting (Mewar Style of painting) or Phad is a stye religious scroll painting and folk painting, practiced in Rajasthan state of India. This is a unique scroll making folk art; this style of painting is traditionally done on a long piece of cloth or canvas, known as phad. It is synonymous with the Bhopa community of the state. These are beautiful specimen of the Rajasthani cloth paintings. The narratives of the folk deities of Rajasthan, mostly of Pabuji and Devnarayan- who are worshipped as the incarnation of lord Vishnu & Laxman. Each hero-god has a different performer-priest or Bhopa. The repertoire of the bhopas consists of epics of some of the popular local hero-gods such as Pabuji, Devji, Tejaji, Gogaji, Ramdevji.The Phad also depict the lives of Ramdev Ji, Rama, Krishna, Budhha & Mahaveera. The iconography of these forms has evolved in a distinctive way. Shahpura in Bhilwara district of Rajasthan are widely known as the traditional artists of this folk art-form for the last two centuries. Presently, Shree Lal Joshi, Nand Kishor Joshi, Prakash Joshi and Shanti Lal Joshi are the most noted artists of the phad painting, who are known for their innovations and creativity. Noted examples of this art are Devnarayan Ki Phad and Pabuji Ki Phad.